Women in focus: an evaluation ; a report for South West Scotland community justice authority - Burgess, Cheryl (Report, 2011)
Women in Focus was introduced in South West Scotland as a partnership between Criminal Justice Social Work Services and Barnardo’s, aimed at supporting women on court orders to complete these orders and to avoid custody through breach. Support workers from Barnardo’s were located in criminal justice social work offices, and using a mentoring-style approach, Women in Focus provided support for women to meet the requirements of court orders and to access community resources aimed at supporting them in the longer-term. The development and operation of Women in Focus resulted from the concerns that many practitioners, policy-makers and others have expressed in relation to the increasing imprisonment of women in Scotland (and internationally). The report sets out the mentoring approach introduced and examines issues arising from the implementation and operation of the service. The report also attempts to evaluate the effectiveness of the service in terms of increased community re/integration and reductions in breach and reoffending. However, innovative attempts, while making a significant difference to the individual women who are able to access them, are introduced and required to operate within, a wider social, political and economic context that can influence how services operate (i.e. short-term funding imposes its own constraints) and how ‘effective’ these innovative services can be seen to be.